The Restoration of Vitamin D Levels Slows the Progression of Renal Ischemic Injury in Rats Previously Deficient in Vitamin D - dos Santos, Michele Santiago; Canale, Daniele; Bernardo, Desiree Rita Denelle; Shimizu, Maria Heloisa Massola; Seguro, Antonio Carlos; Volpini, Rildo Aparecido; de Bragança, Ana Carolina (Frontiers in Medicine, 2021)
Chronic kidney disease (CKD) remains a global public health problem. The initial damage after ischemia/reperfusion (I/R) injury plays an important role in the pathogenesis of acute kidney injury (AKI) and predisposition to CKD. Several studies have been showing that nontraditional risk factors such as AKI and hypovitaminosis D could also be involved in CKD progression. Vitamin D deficiency (VDD) is associated with hemodynamic changes, activation of inflammatory pathways and renal disease progression (RDP) following I/R-AKI. Strategies for prevention and/or slowing RDP have been determined and the sufficiency of vitamin D has been emerging as a renoprotective factor in many diseases. Therefore, we investigated the effect of the restoration of vitamin D levels in the progression of I/R injury (IRI) in rats previously deficient in vitamin D. On day 30, male Wistar rats were submitted to bilateral 45 min IRI and divided into three groups: IRI, standard diet for 120 days; VDD+IRI, vitamin D-free diet for 120 days; and VDD+IRI+R, vitamin D-free diet in the first 30 days and just after I/R, we reintroduced the standard diet in the last 90 days. After the 120-day protocol, VDD+IRI+R rats presented an improvement in the renal function and renal protein handling followed by a smaller fractional interstitial area. Furthermore, those animals exhibited a reestablishment regarding the hemodynamic parameters and plasma levels of aldosterone, urea and PTH. In addition, the restoration of vitamin D levels reestablished the amount of MCP1 and the renal expressions of CD68+ and CD3+ cells in the VDD+IRI+R rats. Also, VDD+IRI+R rats showed a restoration regarding the amount of collagen type III and renal expressions of fibronectin, vimentin and α-SMA. Such changes were also accompanied by a reestablishment on the renal expression of VDR, Klotho, JG12 and TGF-β1. Our findings indicate that the restoration of vitamin D levels not only improved the renal function and hemodynamics but also reduced the inflammation and fibrosis lesions observed in I/R-AKI associated with VDD. Thus, monitoring of vitamin D status as well as its replacement in the early stages of kidney injury may be a therapeutic alternative in the mitigation of renal disease progression.